Macroeconomic factors for the global competitiveness of latin american countries (2013-2023) - Flores-Sotelo, Willian Sebastian; Paredes-Taipe, Francisco Aquilino; Flores-Palomino, Floresmilo; Zarate Hermoza, Jesus Roberto (Revista Venezolana de Gerencia, 2026)
Latin America faces persistent global competitiveness gaps that limit its economic development, evidenced by lagging indicators compared to other regions. The lack of consensus on the determining macroeconomic factors in the Latin American context justifies this research, which seeks to identify those with a significant impact on regional competitiveness over the last decade. Using a quantitative design based on secondary data analysis from representative countries, variables such as trade openness, infrastructure investment, educational quality, inflation, and institutional stability were examined. The results showed that trade openness and investment in education are determining factors, while inflation and foreign direct investment did not present statistically significant impacts. Marked competitive disparities between countries were identified, associated with differences in their macroeconomic policies. The study provides empirical evidence to guide effective public policies, contributing to both academic debate and decision-making by policymakers and business leaders interested in improving regional competitive sustainability.